FLARE STARS IN THE ORION NEBULA REGION - HARO, G; CHAVIRA, E (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1971)
During 1965-1969 we obtained at the Tonantzintla Observatory a large number of multiple exposure photographic plates where 78 new flare stars were detected. In this work we present identification charts for the 254 known flare stars, we discuss some of th
BOL OBS TONAN TACUB
Keywords: FLARE STARS, ORION, NEBULA, REGION; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS